Cerebral gliomas and metastases: assessment with contrast-enhanced fast fluid-attenuated inversion-recovery MR imaging - Essig, Marco; Knopp, Michael V.; Hawighorst, Hans; Debus, Jürgen; Kaick, Gerhard van; Schönberg, Stefan; Wenz, Frederik (Radiology, 1999)
The effect of contrast material on fast fluid-attenuated inversion-recovery (FLAIR) magnetic resonance images was evaluated for 16 patients with enhancing gliomas and 12 patients with cerebral metastases. Because of a marked T1 effect, fast FLAIR imaging provided a marked contrast enhancement, resulting in the highest tumor-to-background contrast ratio compared with standard imaging techniques.